Oat avenanthramide B alleviates high-fat diet-induced obesity via regulating fatty acid metabolism involved in gut bacteria and fungi remodeling - Yongyong Liu; Kai Huang; Xiao Guan; Sen Li; Hongdong Song; Ying Zhang; Yu Zhang; Zhu Sun; Zhiquan Yu (Food Science and Human Wellness)
Oat avenanthramides (AVNs) have been found to exhibit novel lipid-lowering effects. However, the mechanism remains unclear. In this study, the effect of avenanthramide B (AVN B), as one of the major AVNs, on high-fat diet (HFD)-induced mice was investigated. Results showed that AVN B significantly inhibited weight gain and improved hepatic and serum lipid biochemical indices. Hepatic RNA-sequencing analysis suggested that AVN B significantly modulates fatty acid (FA) metabolism. Hepatic real-time qualitative polymerase chain reaction (RT-qPCR) and Western blot results indicated that AVN B could alleviate FA synthesis by activating the adenosine 5’-monophosphate (AMP)-activated protein kinase (AMPK)-sterol regulatory element binding protein-1c (SREBP1c)-fatty acid synthase (FAS), and increase FA oxidation by activating the AMPK/carnitine palmitoyltransferase 1A (CPT1A) and peroxisome proliferator-activated receptor α (PPARα). Additionally, AVN B had a regulating effect on ileum lipid metabolism by inhibiting intestinal cell differentiation and down-regulating the expression levels of FA absorption-related protein and gene. Moreover, AVN B promoted the growth of beneficial bacteria and fungi such as Coriobacteriaceae_UCG-002, Parvibacter, Enterococcus, and Aspergillus, while decreasing the abundance of Roseburia, unclassified_f_Lachnospiraceae, Cladosporium, Eurotium, unclassified_f_Aspergillaceae and unclassified_f_Ceratocystidaceae. All these results provided new points of the lipid-lowing mechanism of AVNs and oats via the gut-liver axis.